2013
DOI: 10.4049/jimmunol.1201174
|View full text |Cite
|
Sign up to set email alerts
|

Fam65b Is a New Transcriptional Target of FOXO1 That Regulates RhoA Signaling for T Lymphocyte Migration

Abstract: Forkhead box O (FOXO) transcription factors favor both T cell quiescence and trafficking through their control of the expression of genes involved in cell cycle progression, adhesion, and homing. In this article, we report that the product of the fam65b gene is a new transcriptional target of FOXO1 that regulates RhoA activity. We show that family with sequence similarity 65 member b (Fam65b) binds the small GTPase RhoA via a noncanonical domain and represses its activity by decreasing its GTP loading. As a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 33 publications
6
49
0
Order By: Relevance
“…1B). Recently, Rougerie et al have shown that FAM65B directly binds to and inhibits RHOA (Rougerie et al, 2013). We confirmed that FAM65B was a potent inhibitor of RHOA, because FAM65B overexpression reduced the amount of active RHOA detected by the RBD pulldown assay (supplementary material Fig.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…1B). Recently, Rougerie et al have shown that FAM65B directly binds to and inhibits RHOA (Rougerie et al, 2013). We confirmed that FAM65B was a potent inhibitor of RHOA, because FAM65B overexpression reduced the amount of active RHOA detected by the RBD pulldown assay (supplementary material Fig.…”
Section: Resultssupporting
confidence: 69%
“…It directly binds to RHOA and blocks the loading of GTP to RHOA. It was also shown that it has a role in chemokine-stimulated migration and adhesion of Jurkat cells (Rougerie et al, 2013). In this study, we confirm FAM65B as being a RHOA inhibitor.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Yeast two-hybrid experiments suggested that FAM65B interacts with NCAM (MIM116930), a membrane-bound glycoprotein that plays a role in cell-cell and cell-matrix adhesion, which is consistent with a role of FAM65B in myoblast fusion (19). In T lymphocytes, FAM65B down-regulates adhesion, polarization, and migration (21). This effect appears to be mediated by inhibition of RHOA (MIM165390), a protein that regulates remodeling of the actin cytoskeleton during cell morphogenesis and hence influences motility.…”
Section: Fam65b Is Present In Apical Plasma Membrane Of Mammalian Hairmentioning
confidence: 54%
“…Notably, most of the studies describe proadhesive signaling events, even when antiadhesive signals likely have an equally relevant role in leukocyte recruitment, for example, during the on-off turnover of integrin activation necessary for cell motility and transmigration. To date, few signaling molecules have been shown to negatively regulate leukocyte integrin activation; these include PKA (34), RHOH (35), CDC42 (10,36), SRC (37-39), H-RAS (40), ILK (41), FAM65B (42), and CAPN2 (43), with only CDC42 investigated according to the previously formalized four criteria (2). In the present study, fully compliant with these criteria, we show that PTPRG is a novel negative regulator of LFA-1 high-affinity-state triggering and mediated arrest by chemoattractants in human primary monocytes.…”
Section: Discussionmentioning
confidence: 99%